Increased serum methylmalonic acid levels were associated with the presence of cardiovascular diseases - Wang, Xiaoya; Li, Wudi; Xiang, Meixiang (Frontiers in Cardiovascular Medicine, 2022)
Background: Functional vitamin B12 deficiency is common in cardiovascular diseases, such as heart failure and myocardial infarction. Methylmalonic acid is a specific and sensitive marker of vitamin B12 deficiency. However, there are scarce data in regard to the relationship between methylmalonic acid and cardiovascular diseases. Methods: In this cross-sectional study, we analyzed data of 5313 adult participants of the National Health and Nutrition Examination Survey (NHANES) 2013-2014. Associations between methylmalonic acid and other variables were assessed with linear regression models. Univariable and multivariable logistic regression models were employed to explore the association between methylmalonic acid and cardiovascular diseases. Results: The weighted prevalence of cardiovascular diseases was 8.8% in the general population of the United States. Higher methylmalonic acid levels were found in participants with cardiovascular diseases (p＜0.001). Linear regression models revealed positive associations between serum methylmalonic acid level and age (p＜0.001), glycohemoglobin (p=0.023), fasting glucose (p=0.044), mean cell volume (p=0.038) and hypertension (p=0.003). In the multivariable logistic model adjusting for age, gender, ethnicity, smoking, hypertension, glycohemoglobin, body mass index (BMI), low-density lipoprotein-cholesterol (LDL-C), renal dysfunction and vitamin B12, serum methylmalonic acid (adjusted odds ratio, 3.08; 95% confidence interval: 1.63~5.81, p=0.002, per ln mg/L increment) was associated with cardiovascular diseases. Conclusion: Our study demonstrated that elevated serum methylmalonic acid levels were independently associated with the presence of cardiovascular diseases and may be used to predict the occurrence of cardiovascular diseases.